Missing and decayed teeth, oral hygiene and dental staining in relation to esophageal cancer risk: ESCCAPE case‐control study in Kilimanjaro, Tanzania. Issue 10 (22nd December 2020) - Mmbaga, Blandina T.; Mwasamwaja, Amos; Mushi, Godfrey; Mremi, Alex; Nyakunga, Gissela; Kiwelu, Ireen; Swai, Remigi; Kiwelu, Godwin; Mustapha, Sophia; Mghase, Eliawawomy; Mchome, Amana; Shao, Redfan; et al.
Abstract: In the African esophageal squamous cell carcinoma (ESCC) corridor, recent work from Kenya found increased ESCC risk associated with poor oral health, including an ill‐understood association with dental fluorosis. We examined these associations in a Tanzanian study, which included examination of potential biases influencing the latter association. This age and sex frequency‐matched case‐control study included 310 ESCC cases and 313 hospital visitor/patient controls. Exposures included self‐reported oral hygiene and nondental observer assessed decayed+missing+filled tooth count (DMFT index) and the Thylstrup‐Fejerskov dental fluorosis index (TFI). Blind to this nondental observer TFI, a dentist independently assessed fluorosis on photographs of 75 participants. Odds ratios (ORs) are adjusted for demographic factors, alcohol and tobacco. ESCC risk was associated with using a chewed stick to brush teeth (OR 2.3 [95% CI: 1.3‐4.1]), using charcoal to whiten teeth (OR 2.13 [95% CI: 1.3, 4.1]) and linearly with the DMFT index (OR 3.3 95% CI: [1.8, 6.0] for ≥10 vs 0). Nondental observer‐assessed fluorosis was strongly associated with ESCC risk (OR 13.5 [95% CI: 5.7‐31.9] for TFI 5+ v 0). However, the professional dentist's assessment indicated that only 43% (10/23) of participants assessed as TFI 5+ actually had fluorosis. In summary, using oral charcoal, brushing with a chewed stick and missing/decayed teeth may be risk factors for ESCC in Tanzania, for which dose‐response and mechanistic research is needed. Links of ESCC with "dental fluorosis" suffered from severe exposure misclassification, rendering it impossible to disentangle any effects of fluorosis, extrinsic staining or reverse causality. Abstract : What's new? The putative etiological model for the African oesophageal cancer corridor involves a combination of unknown spatially‐patterned factors and lifestyle factors such as poor oral health. The association of oesophageal cancer with dental fluorosis in Kenya, in addition to expected associations with dental decay/loss, recently raised intrigue. In the present Tanzanian case‐control study, findings were consistent with those from Kenya. However, a review of oral photographs indicated serious fluorosis exposure misclassification, rendering it impossible to disentangle any effects of fluorosis, extrinsic staining, or reverse causality.